Changes in mouse gut bacterial community in response to different types of drinking water. (1st April 2018) - Dias, Marcela F.; Reis, Mariana P.; Acurcio, Leonardo B.; Carmo, Anderson O.; Diamantino, Cristiane F.; Motta, Amanda M.; Kalapothakis, Evanguedes; Nicoli, Jacques R.; Nascimento, Andréa M.A.
Abstract: Gut microbiota exerts a fundamental role on host physiology, and how extrinsic perturbations influence its composition has been increasingly examined. However, the effect of drinking water on gut microbiota is still poorly understood. In this study, we explored the response of mouse gut bacterial community (fecal and mucosa-adhered) to the ingestion of different types of drinking water. The experimental cohort was divided according to different water sources into four groups of mice that consumed autoclaved tap water (control group), water collected directly from a drinking water treatment plant, tap water, and commercial bottled mineral water. Differences among groups were observed, especially related to control group, which exhibited the smallest intra-group variation, and the largest distance from test groups on the last experimental day. Clinically important taxa, such as Acinetobacter and Staphylococcus, increased in feces of mice that drank tap water and in mucosa-adhered samples of animals from disinfected and tap water groups. Furthermore, statistical analyses showed that both time elapsed between samplings and water type significantly influenced the variation observed in the samples. Our results reveal that drinking water potentially affects gut microbiota composition. Additionally, the increase of typical drinking water clinically relevant and antibiotic resistance-associated bacteria in gut microbiota is a cause of concern. Highlights: The effect of different drinking waters on mouse gut microbiota was investigated. Consumption of autoclaved water was associated with more homogeneous microbiota. A significant increase of antibiotic-resistant bacteria in the gut is a cause of concern. Time and drinking water type significantly affected gut bacterial profile.